Penipuan Hadiah Melalui Short Message Service (SMS) sebagai Bentuk Penyalahgunaan Teknologi Informasi - Simanjuntak Simanjuntak; Maylisa Lisdiana (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The advancement of information technology has increased very rapidly, one of which can be seen from the use of cell phones as the main communication tool. However, this progress also creates a gap, for the emergence of cybercrime such as fraud through short messages or called Short Message Service (SMS). Fraud via SMS by offering prizes is one form of misuse of information technology that is increasingly prevalent in the digital era. This mode of fraud is often carried out because it takes advantage of the lack of public awareness of information security and tends to target individuals who do not understand how communication technology works. This article discusses how the mechanism of fraud carried out via SMS, the impact caused to victims, and how legal regulations in Indonesia handle prize fraud via SMS. This research uses normative research methods conducted through data collection from various references including journals and laws and regulations. This research is expected to provide a more comprehensive understanding of the role of law in tackling SMS-based fraud and offer solutions that can strengthen consumer protection in the digital era.